'A lipaemic mystery': a patient with hypertriglyceridaemic pancreatitis and cerebral infarction. (20th December 2011) - King, Patricia; Smith, Philip Joseph; Betteridge, John; Brown, Mike
Abstract : Hypertriglyceridaemia (HTG) causes up to 10% of all cases of acute pancreatitis (AP). It is the third most common cause after gallstones and alcohol. Despite this frequency, there are no clear guidelines for its specific management, mainly due to the paucity of evidence. The authors present a case and discussion of hypertriglyceridaemic pancreatitis (HTGP) complicated by an acute cerebral infarct. The patient's subsequent death secondary to cerebral infarction opens the discussion as to whether HTG should be more urgently treated.